Underfill material for micro-LED display element, underfill film, method for manufacturing underfill film, and micro-LED display element

By using an underfill material prepared by using an adhesive composition containing a phenolic hydroxyl resin, isocyanurate and epoxy compound, the problems of large amount of LED elements transfer and low metal bonding efficiency and electrode peel corrosion in the micro LED display element are solved, and efficient manufacturing and high-quality micro LED display element are achieved.

CN119546667APending Publication Date: 2025-02-28NISSAN CHEM CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480003374.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-29
Filing Date
2024-03-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the manufacturing process of micro LED display elements, the large amount of transfer and metal bonding efficiency of LED elements in the prior art is low, and the underfill material is prone to electrode peeling and corrosion due to external stress and moisture, making it difficult to maintain high transparency and heat resistance.

Method used

An adhesive composition comprising an alkali-soluble resin having a phenolic hydroxyl group, a compound of isocyanurate backbone, an aliphatic or alicyclic epoxy compound and a solvent is prepared from which the composition is prepared a bottom-filled material with a melting function, high adhesion at room temperature, heat resistance to yellowing inhibition and film formation only in a specific area.

Benefits of technology

The efficiency of huge transfer of LED elements and metal bonding is improved, the fusing and adhesion of the underfill material is enhanced, high transparency and heat resistance are ensured, electrode peeling and corrosion are avoided, and the overall quality of micro LED display elements is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005236417770000041
    Figure BDA0005236417770000041
  • Figure BDA0005236417770000071
    Figure BDA0005236417770000071
  • Figure BDA0005236417770000101
    Figure BDA0005236417770000101
Patent Text Reader

Abstract

The purpose of the present invention is to provide: an underfill material which has a fluxing function, sufficient adhesive strength at room temperature, and resistance to thermal yellowing in a high-temperature process, and which is capable of forming a film only in a specific region, in order to enable the mass transfer of LED elements, the efficiency of metal bonding, and the high-quality grading of LED display elements; also provided are an underfill film, a method for manufacturing the underfill film, and a micro-LED display element provided with the underfill film, the underfill film being patterned on an array substrate, the underfill film being capable of mass transfer of an LED element and efficiency of metal bonding using the underfill film, a method for manufacturing the underfill film, and a micro-LED display element provided with the underfill film. A heat-curable adhesive composition containing component (A), component (B), component (C), and component (D) described below. Component (A): an alkali-soluble resin having a phenolic hydroxyl group and a polymer glass transition temperature (Tg) of 60 DEG C or less. Component (B): a compound having an isocyanurate skeleton. Component (C): an aliphatic or alicyclic epoxy compound. Component (D): a solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an underfill material, an underfill film, a method for manufacturing an underfill film, and a micro-LED display element for a micro-LED display element, and in particular to an underfill material, an underfill film, a method for manufacturing an underfill film, a underfill film obtained by the manufacturing method, and a micro-LED display element using the underfill film. Background Art

[0002] Currently, liquid crystal display elements (LCD: Liquid Crystal Display) and organic light-emitting diode display elements (OLED: Organic Light-Emitting Diode) are mainly used in flat-panel displays for portable phones, monitors, and televisions. The mass production technology of LCD has been fully established, and it is cheap and can be large-scale. On the other hand, the display requires the use of a backlight, so the form factor and flexibility are poor. In addition, although OLED has excellent flexibility, there is a problem that the life span becomes shorter if the brightness of the display element is increased. As a display element that can solve these shortcomings, in recent years, a micro-LED display element has been developed that arranges inorganic light-emitting diodes on each pixel of an array substrate for display. Micro-LED display elements use micron-sized inorganic light-emitting diodes as light sources, so compared with LCD and OLED, they can improve brightness, have high color purity, and have a long life. In addition, LEDs are arranged in each pixel, so each pixel can be made independent and has excellent flexibility.

[0003] The LED element of the light source is cut into small pieces after the semiconductor layer is epitaxially grown on a sapphire substrate to form an electrode. The micro-LED display element requires the LED elements manufactured in this way to be arranged on an array substrate with high precision. As a method of arranging LED elements on an array substrate, a pick-and-place method of arranging each LED element one by one has been studied in the past. However, in this method, the setting of the LED takes a lot of time, so it is not suitable for mass production.

[0004] Therefore, in recent years, a stamp method has been proposed, that is, a large number of LED components are picked up from a sapphire substrate at one time using an adhesive substrate (stamp), and after mass transfer to an array substrate, a bonding head is used to heat-press the LED components to the electrodes of the array substrate, or laser heating is used for metal bonding (non-patent literature 1, 2). If this method is used, a large number of LED components can be arranged on the array substrate at one time and bonded to the array substrate, so it is estimated that the production volume will be greatly improved compared to the pick-and-place method.

[0005] Prior art literature

[0006] Non-patent literature

[0007] Non-patent document 1: Adv. Optical Mater. 2015, 3, 1313-1335

[0008] Non-patent document 2: SID 2017 DIGEST, 257 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In the mass transfer method using a stamp, the LED elements are mass transferred from the sapphire substrate to the array substrate by utilizing the difference between the adhesiveness between the array substrate and the LED elements and the adhesiveness between the stamp and the LED elements, so an adhesive component is required on the array substrate. The adhesive component mostly serves to bond the LED elements to the substrate electrodes, so solder paste or conductive paste is usually used. However, in this case, a space is formed around the electrodes of the LED elements, and the peeling and corrosion of the electrodes caused by external stress applied to the panel by vibration, etc., moisture, etc. become a problem.

[0011] Among the adhesive components, the non-conductive paste and film are repelled from between the LED electrode and the array substrate electrode when the LED element is bonded to the paste and film to join the LED element to the substrate electrode, and remain as a permanent film around the electrode, thereby functioning as a bottom filling material that protects the electrode periphery from moisture and external stress. It is therefore expected that the above-mentioned problems can be improved.

[0012] Another problem unique to micro-LED display elements is the heat-resistant yellowing suppression of components around LED elements. The light from the LED element diffuses not only in the vertical direction to the substrate, but also in all directions. Therefore, in order to maintain the color purity of the LED element, the transparency of the peripheral components is required. And as mentioned above, when the LED element is metal-bonded to the electrode of the array substrate, high-temperature processes such as thermal compression and laser heating are used. Therefore, the components around the LED element are required to be able to maintain high transparency even after this high-temperature process.

[0013] Next, as a problem that is not unique to micro-LED display elements but common to semiconductor mounted devices, the fluxing process for removing the oxide film on the electrode portion can be cited. In micro-LED display elements, if an oxide film is formed on the electrode portion of the array substrate or LED element, metal bonding cannot be performed and poor conduction occurs. Usually, a flux containing volatile low molecular weight is used to remove the oxide film, but if the volatile low molecular weight remains between the electrodes after the fluxing process, there is a problem of electrode corrosion.

[0014] In addition, if a functional film is formed on the entire surface of an array substrate or a chip, there is also the problem of difficulty in removing the wiring afterwards. Therefore, a bottom filling material with non-volatility and fluxing function is required, which can form a film only in a specific area by utilizing patterning of photolithography, inkjet coating, and pattern pasting of a film sheet.

[0015] Therefore, an object of the present invention is to provide an underfill material having the following functions in order to enable mass transfer of LED elements and efficiency of metal bonding and high quality grade of LED display elements.

[0016] (1) It has a fluxing function.

[0017] (2) It exhibits sufficient adhesive strength at room temperature.

[0018] (3) Heat-resistant yellowing inhibition in high-temperature processes.

[0019] (4) A film is formed only in a specific area.

[0020] Another object of the present invention is to provide an underfill film that is patterned on an array substrate, and by using the underfill material, mass transfer of LED elements and efficient metal bonding can be performed.

[0021] Furthermore, an object of the present invention is to provide a method for producing an underfill film, wherein the underfill material is used to enable mass transfer of LED elements and efficient metal bonding.

[0022] Furthermore, an object of the present invention is to provide a micro LED display element, which includes the above-mentioned underfill film, and the underfill film can perform mass transfer of LED elements and improve the efficiency of metal bonding.

[0023] Solutions for solving problems

[0024] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found the present invention as a result. That is, the present invention relates to the following contents.

[0025] 1. An adhesive composition comprising the following components (A), (B), (C) and (D).

[0026] (A) Component: an alkali-soluble resin having a phenolic hydroxyl group and a polymer having a glass transition temperature (Tg) of 60° C. or less.

[0027] (B) Component: a compound having an isocyanurate skeleton.

[0028] Component (C): an aliphatic or alicyclic epoxy compound.

[0029] (D) Component: solvent.

[0030] 2. The adhesive composition according to 1, wherein the component (A) is a polymer including a structural unit derived from a monomer (A2) having a homopolymer Tg of 0° C. or less.

[0031] 3. The adhesive composition according to 2, wherein the component (A) is an acrylic polymer containing structural units as constituent components, wherein the structural units are derived from a monomer (A1) having a phenolic hydroxyl group and a polymerizable unsaturated group and a monomer (A2) having a homopolymer Tg of 0°C or less.

[0032] 4. The adhesive composition according to 3, wherein the monomer (A1) having a phenolic hydroxyl group and a polymerizable unsaturated group is selected from the group consisting of p-hydroxystyrene, m-hydroxystyrene, α-methyl-p-hydroxystyrene, and a compound represented by the following formula (1).

[0033] P-b1-c1-d1 (1)

[0034] In the formula, P represents a (meth)acryloyl group, a (meth)acrylamide group, an N-methyl(meth)acrylamide group or a maleimide group, b1 represents a single bond, or an alkylene group consisting of a linear, branched or cyclic group having 1 to 12 carbon atoms and a combination thereof, c1 represents a single bond, -O-, -COO- or -OCO-, and d1 represents a substituted or unsubstituted hydroxyphenyl group.

[0035] 5. The adhesive composition according to 3 or 4, wherein the monomer (A2) having a homopolymer Tg of 0°C or less is a compound represented by the following formula (2).

[0036]

[0037] In the formula, R2 represents a hydrogen atom or a methyl group, a2 represents an oxygen atom or a sulfur atom, b2 represents an alkylene group consisting of a straight chain, branched chain or cyclic group or a combination thereof having 2 to 20 carbon atoms, and the -CH2- in the alkylene group is optionally substituted with an oxygen atom on the premise that they are not adjacent to each other. c2 represents a single bond, -O-, -COO- or -OCO-, and d2 represents a hydrogen atom or a hydroxyl group.

[0038] 6. The adhesive composition according to any one of 1 to 5, wherein the component (B) is 20 to 100 parts by mass based on 100 parts by mass of the component (A). (Optimum Amount of Isocyanurate Component)

[0039] 7. The adhesive composition according to any one of 1 to 6, wherein the component (C) is 10 to 100 parts by mass based on 100 parts by mass of the component (A). (Optimal Amount of Other Epoxy Components)

[0040] 8. The adhesive composition according to any one of 1 to 7, further comprising 0.01 to 1.0 parts by mass of a surfactant as the component (E), based on 100 parts by mass of the component (A).

[0041] 9. The adhesive composition according to any one of 1 to 8, further comprising an inorganic filler as component (F).

[0042] 10. An adhesive sheet obtained by laminating the adhesive composition according to any one of 1 to 9 on both sides with a release substrate.

[0043] 11. A cured film obtained by curing the adhesive composition according to any one of 1 to 9.

[0044] 12. An LED display element comprising the cured film according to 11 as an underfill material.

[0045] Effects of the Invention

[0046] The adhesive composition of the present invention has excellent film transparency with fluxing property, adhesive property and heat-resistant yellowing, and can form an underfill material capable of mass transfer of LED components and efficient metal bonding. Moreover, the underfill film can be formed in the form of a film only on the required part of the array substrate. DETAILED DESCRIPTION

[0047] The adhesive composition of the present invention contains the following (A) component, (B) component, (C) component, and (D) component.

[0048] Component (A): a resin having a phenolic hydroxyl group and a polymer having a glass transition temperature (Tg) of 60° C. or less.

[0049] (B) Component: a compound having an isocyanurate skeleton.

[0050] (C) Component: an epoxy compound having an aliphatic or alicyclic skeleton.

[0051] (D) Component: solvent.

[0052] Hereinafter, the details of each component will be described.

[0053] <(A)Component>

[0054] The component (A) is a resin having a phenolic hydroxyl group and a polymer having a glass transition temperature (Tg) of 60° C. or less, and specifically, an alkali-soluble resin. The alkali-soluble resin is preferably an acrylic polymer.

[0055] In the present invention, the acrylic polymer refers to a polymer obtained using a monomer having a polymerizable unsaturated group, ie, a polymerizable group containing a carbon-carbon double bond in its structure, such as acrylate, methacrylate, styrene, and maleimide.

[0056] The resin of the component (A) is not particularly limited in terms of the main chain skeleton and the type of side chains constituting the acrylic polymer.

[0057] If the resin of component (A) is a resin with a weight average molecular weight of less than 20,000, the peelability from the peeling substrate is easily deteriorated when making a sheet. On the other hand, if the resin of component (A) is a resin with a weight average molecular weight of more than 150,000, the flexibility of the film is impaired, and the resin repellency during flip chip bonding is deteriorated. From these viewpoints, the preferred weight average molecular weight of the above resin is in the range of 20,000 to 150,000, and more preferably in the range of 30,000 to 100,000.

[0058] As for the synthesis method of the resin of component (A), a method of copolymerizing a monomer mixture containing a monomer (A1) having a phenolic hydroxyl group and a polymerizable unsaturated group and a monomer (A2) having a homopolymer Tg of 0°C or less is simple. Here, the homopolymer refers to a polymer of the (A2) monomer alone, which is a polymer having a weight average molecular weight of 3,000 or more obtained by: performing a polymerization reaction at a temperature of 50 to 110°C in a solvent in which a polymerization initiator or the like is coexisted as desired; or by irradiating the (A2) monomer with ultraviolet rays in the coexistence of a photoradical generator or the like to perform a polymerization reaction.

[0059] The details of the monomers constituting the component (A) will be described below.

[0060] The monomer (A1) is a monomer having a phenolic hydroxyl group and a polymerizable unsaturated group, and is preferably at least one monomer selected from p-hydroxystyrene, m-hydroxystyrene, α-methyl-p-hydroxystyrene and a compound represented by the following formula (1).

[0061] P-b1-c1-d1 (1)

[0062] In formula (1), P represents a (meth)acryloyl group, a (meth)acrylamide group, an N-methyl(meth)acrylamide group or a maleimide group, preferably a (meth)acryloyl group. b1 represents a single bond, or an alkylene group consisting of a linear, branched or cyclic group having 1 to 12 carbon atoms or a combination thereof, preferably a single bond or a linear alkylene group having 1 to 6 carbon atoms. c1 represents a single bond, -O-, -COO- or -OCO-, preferably a single bond or -O-. d1 represents a substituted or unsubstituted hydroxyphenyl group, preferably a p-hydroxyphenyl group. Examples of substituents for the hydroxyphenyl group include a halogen atom, an alkyl group having 1 to 3 carbon atoms, an alkenyl group having 2 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a fluoroalkyl group having 1 to 3 carbon atoms, a fluoroalkenyl group having 2 to 3 carbon atoms, a fluoroalkoxy group having 1 to 3 carbon atoms, an alkoxycarbonyl group having 2 to 3 carbon atoms, a cyano group, a nitro group, and the like. By having these hydroxyphenyl groups, the component (A) exhibits fluxing properties.

[0063] Examples of the monomer (A1) include p-hydroxystyrene, α-methyl p-hydroxystyrene, N-(p-hydroxyphenyl)maleimide, N-(p-hydroxyphenyl)acrylamide, N-(p-hydroxyphenyl)methacrylamide, p-hydroxyphenyl acrylate, and p-hydroxyphenyl methacrylate, and these monomers may be used alone or in combination of two or more. Among these, monomers selected from p-hydroxyphenyl acrylate and p-hydroxyphenyl methacrylate are preferred.

[0064] The monomer (A2) is a monomer having a homopolymer Tg of 0°C or lower, and is preferably a compound represented by the following formula (2).

[0065]

[0066] In formula (2), R2 represents a hydrogen atom or a methyl group. a2 represents an oxygen atom or a sulfur atom, preferably an oxygen atom. b2 represents an alkylene group consisting of a straight chain, branched chain or cyclic group and a combination thereof having 2 to 20 carbon atoms, preferably an alkylene group consisting of a straight chain, branched chain or cyclic group and a combination thereof having 2 to 12 carbon atoms, more preferably a straight chain or branched chain alkylene group having 2 to 12 carbon atoms. It should be noted that -CH2- in the alkylene group of b2 is optionally substituted with an oxygen atom on the premise that they are not adjacent to each other. c2 represents a single bond, -O-, -COO- or -OCO-, preferably a single bond or -O-. d2 represents a hydrogen atom or a hydroxyl group.

[0067] Specific examples of the monomer (A2) include ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, tert-butyl acrylate, n-pentyl acrylate, n-hexyl acrylate, n-hexyl methacrylate, n-heptyl acrylate, n-heptyl methacrylate, n-octyl acrylate, n-octyl methacrylate, nonyl acrylate, nonyl methacrylate, isononyl acrylate, isononyl methacrylate, lauryl acrylate, lauryl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl meth ...acrylate, 2-hydroxyethyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 3-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, ethyl carbitol acrylate, glycidyl acrylate, methoxytriethylene glycol acrylate, methoxytriethylene glycol methacrylate, 2-methoxyethyl acrylate, 2-methoxyethyl methacrylate, 2-ethoxyethyl acrylate, 2-ethoxyethyl methacrylate, tetrahydrofurfuryl acrylate, 3-methoxybutyl acrylate, 3-methoxybutyl methacrylate, diethylene glycol monoacrylate, diethylene glycol monomethacrylate, etc., which can be used alone or in combination of two or more, but are not limited thereto.

[0068] From the viewpoint of appropriately obtaining the effects of the present invention, the structural units derived from the monomer (A1) in the component (A) preferably contain 10 to 50% by mass relative to the total of the structural units derived from the monomer (A1) and the structural units derived from the monomer (A2), and the structural units derived from the monomer (A2) in the component (A) preferably contain 50 to 90% by mass relative to the total of the structural units derived from the monomer (A1) and the structural units derived from the monomer (A2).

[0069] In addition, in the present invention, when obtaining the acrylic polymer of component (A), other monomers copolymerizable with the above-mentioned monomers (A1) to (A2) may be used in combination. Specific examples of the above-mentioned other monomers include: acrylate compounds, methacrylate compounds, maleimide, acrylamide compounds, acrylonitrile, styrene compounds, and vinyl compounds. Specific examples of the above-mentioned other monomers are listed below, but are not limited to these.

[0070] Examples of the acrylate compound include methyl acrylate, cyclohexyl acrylate, isobornyl acrylate, 2-methyl-2-adamantyl acrylate, anthracene acrylate, anthracene methyl acrylate, 2,2,2-trifluoroethyl acrylate, 2-aminoethyl acrylate, 2-propyl-2-adamantyl acrylate, 2-(acryloyloxy)ethyl caprolactone, and poly(ethylene glycol) ethyl ether acrylate.

[0071] Examples of the methacrylate compound include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, 2-methyl-2-adamantyl methacrylate, 2-hydroxyethyl methacrylate, glycidyl methacrylate, tetrahydrofurfuryl methacrylate, anthracene methacrylate, anthracenemethyl methacrylate, 2,2,2-trifluoroethyl methacrylate, 2-aminomethyl methacrylate, γ-butyrolactone methacrylate, 2-propyl-2-adamantyl methacrylate, 2-(methacryloyloxy)ethyl caprolactone, and poly(ethylene glycol)ethyl ether methacrylate.

[0072] Examples of the acrylamide compound include N-methylacrylamide, N-methylmethacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N-methoxymethylacrylamide, N-methoxymethylmethacrylamide, N-butoxymethylacrylamide, and N-butoxymethylmethacrylamide.

[0073] Examples of the vinyl compound include methyl vinyl ether, benzyl vinyl ether, cyclohexyl vinyl ether, vinyl naphthalene, vinyl anthracene, vinyl carbazole, allyl glycidyl ether, 3-vinyl-7-oxabicyclo[4.1.0]heptane, 1,2-epoxy-5-hexene, and 1,7-octadiene monoepoxide.

[0074] Examples of the styrene compound include styrenes having no hydroxyl group, for example, styrene, α-methylstyrene, chlorostyrene, bromostyrene, and the like.

[0075] The method for obtaining the alkali-soluble resin used in the present invention is not particularly limited, and it can be obtained, for example, by carrying out a polymerization reaction at a temperature of 50 to 110° C. in a solvent in which monomer (A1) and monomer (A2) and the above-mentioned other monomers and a polymerization initiator are coexistent as desired. In this case, the solvent used is not particularly limited as long as it dissolves the monomers and resin constituting the resin. As specific examples, the solvents described in the (D) solvent described later can be cited.

[0076] The resin thus obtained (hereinafter also referred to as a specific copolymer) is usually in the state of a solution dissolved in a solvent.

[0077] In addition, the solution of the specific copolymer obtained as described above is put into diethyl ether, water, etc. under stirring to make it reprecipitate, and the generated precipitate is filtered / washed, and then dried at room temperature or heated under normal pressure or reduced pressure to prepare a powder of the specific copolymer. Through such an operation, the polymerization initiator and unreacted monomer coexisting with the specific copolymer can be removed, and as a result, a purified powder of the specific copolymer is obtained. In the case where it is not possible to fully purify it by one operation, the obtained powder is redissolved in a solvent and the above operation is repeated.

[0078] In the present invention, the powder of the specific copolymer may be used as it is, or the powder may be used in the form of a solution by, for example, redissolving the powder in the (D) solvent described later.

[0079] Furthermore, in the present invention, the resin of the component (A) may be a mixture of a plurality of specific copolymers.

[0080] <(B) Ingredient>

[0081] The component (B) of the present invention is a compound having an isocyanurate skeleton. By including an isocyanurate skeleton in the composition, high adhesion to metal at room temperature can be achieved. From the perspective of curability, a compound having two or more polymerizable unsaturated double bonds in the isocyanurate skeleton is preferred. The preferred skeleton of the component (B) can be exemplified by formula (4A) and formula (4B) (also referred to as formula (4)).

[0082]

[0083]

[0084] The content of the component (B) in the composition of the present invention is preferably 20 to 100 parts by mass, more preferably 30 to 90 parts by mass, based on 100 parts by mass of the component (A).

[0085] <(C) Ingredients>

[0086] Component (C) is an epoxy compound having an aliphatic or alicyclic skeleton. When the epoxy compound as the crosslinking component in the composition has an aromatic or aminoglycidyl group, the film is easily yellowed by high temperature heating, so an aliphatic or alicyclic skeleton is preferred.

[0087] A preferred skeleton of the component (C) is represented by formula (5) or formula (6).

[0088]

[0089] (In formula (5), k is an integer of 2 to 10, m is an integer of 0 to 4, and X5 represents a k-valent organic group that does not contain an aromatic ring. Multiple m's may be the same or different from each other.)

[0090]

[0091] (In formula (6), k is an integer of 2 to 10, and X6 represents a k-valent organic group not containing an aromatic ring)

[0092] Specific examples of the compound having a cycloolefin oxide structure represented by formula (5) include EPOLEAD GT-401, EPOLEAD GT-403, EPOLEAD GT-301, EPOLEAD GT-302, EPOLEAD PB4700, CELLOXIDE 2021, CELLOXIDE 2081, CELLOXIDE 3000 (trade names manufactured by Daicel Corporation), EPOCHALIC DE-102, DE-103 (each manufactured by ENEOS Corporation), and the like.

[0093] Specific examples of the compound represented by formula (6) include EHPE3150 (trade name, manufactured by Daicel Corporation) of an alicyclic epoxy compound, DENACOL EX-252 (trade name, manufactured by Nagase ChemteX Corporation), ST-3000 and ST-4000D (trade names, manufactured by Nippon Steel Chemical & Material Co., Ltd.) of a hydrogenated glycidyl ether epoxy compound, EPOTEC YDH184 and EPOTEC YDH3000 (trade names, manufactured by Tomoe Industries Co., Ltd.), RIKARESIN HBE-100 (trade name, manufactured by Shin Nippon Rika Co., Ltd.), EPOTEC RD107, EPOTEC RD111, EPOTEC RD114, EPOTEC RD130, EPOTEC RD113 and EPOTEC RD129 (trade names, manufactured by Tomoe Industries Co., Ltd.) of aliphatic ester structure, and Shofree PETG (trade name, manufactured by Resonac Corporation).

[0094] The content of the component (C) in the composition of the present invention is preferably 10 to 100 parts by mass, more preferably 30 to 90 parts by mass, relative to 100 parts by mass of the component (A).

[0095] <(D) Ingredient>

[0096] The (D) solvent used in the present invention is a solvent that dissolves the (A) component, the (B) component, and the (C) component and dissolves various components added as desired, and its type and structure are not particularly limited as long as it has such a dissolving ability.

[0097] Examples of such solvents (D) include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, methyl cellosolve acetate, ethyl cellosolve acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol propyl ether acetate, toluene, xylene, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-butanone, 3-methyl-2-pentanone, 2-pentanone, 2-heptanone, γ-butyrolactone, 2- Ethyl hydroxypropionate, ethyl 2-hydroxy-2-methylpropionate, ethyl ethoxylate, ethyl hydroxylate, methyl 2-hydroxy-3-methylbutyrate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethyl 3-ethoxypropionate, methyl 3-ethoxypropionate, methyl pyruvate, ethyl pyruvate, ethyl acetate, butyl acetate, ethyl lactate, butyl lactate, N,N-dimethylformamide, N,N-dimethylacetamide and N-methyl-2-pyrrolidone, etc.

[0098] Among these (D) solvents, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, 2-heptanone, propylene glycol propyl ether, propylene glycol propyl ether acetate, ethyl lactate, butyl lactate, and the like are more preferred from the viewpoint of good coating properties and high safety.

[0099] Furthermore, other solvents may be mixed in a ratio of 1 to 90 mass %, preferably 1 to 50 mass % of the total solvents used in the varnish for the purpose of improving wettability to the substrate, adjusting the surface tension of the solvent, adjusting polarity, adjusting the boiling point, etc.

[0100] Examples of such solvents include, but are not limited to, methanol, ethanol, isopropanol, diisoamyl ether, and methyl salicylate. These solvents may be used alone or in combination of two or more.

[0101] <(E) Ingredient>

[0102] (E) Component is a surfactant. The composition of the present invention may further contain a surfactant for the purpose of improving its coating properties, unless the effects of the present invention are impaired.

[0103] The surfactant of component (E) is not particularly limited, and examples thereof include fluorine-based surfactants, silicone-based surfactants, nonionic surfactants, etc. As such surfactants, commercial products such as those manufactured by 3M Japan, DIC, or AGC SEIMI CHEMICAL can be used. These commercial products are easily available and therefore convenient. Specific examples thereof include POLYFOX PF-136A, 151, 156A, 154N, 159, 636, 6320, 656, and 6520 (manufactured by Omnova Corporation), MEGAFACE R30, R08, R40, R41, R43, F251, F477, F552, F553, F554, F555, F556, F557, F558, F559, F560, F561, F562, F563, F565, F567, and F570 (manufactured by DIC Corporation), FC4430 and FC4432 (manufactured by 3M Japan Co., Ltd.), AsahiGuard AG710, SURFLON S-386, S-611, and S-651 (manufactured by AGC SEIMI Co., Ltd.), Chemical Co., Ltd.), FTERGENT FTX-218, DFX-18, 220P, 251, 212M, 215M (NEOS Co., Ltd.), BYK-300, 302, 306, 307, 310, 313, 315, 320, 322, 323, 325, 330, 331, 333, 342, 345, 346, 347, 348, 349, 370, 377, 378, 3455 (BYK Chemie Japan Co., Ltd.), SH3746, SH3749, SH3771, SH8400, SH8410, SH8700, SF8428 (Dow Corning Toray Silicone Co., Ltd.), KF-351, KF-352, KF-353, KF-354L, KF-355A, KF-615A, KF-945, KF-618, KF-6011, KF-6015 (manufactured by Shin-Etsu Chemical Co., Ltd.), and other silicone-based surfactants.

[0104] The surfactant of the component (E) may be used alone or in combination of two or more.

[0105] When using a surfactant, the content thereof is usually 0.01 to 1.0 part by mass, preferably 0.02 to 0.8 part by mass based on 100 parts by mass of the component (A).

[0106] <(F)Component>

[0107] Component (F) is an inorganic filler. The composition of the present invention may further contain an inorganic filler for the purpose of improving the transparency of the film and the hardness of the cured film, unless the effects of the present invention are impaired.

[0108] The inorganic filler as component (F) is not particularly limited, and examples thereof include sols of silicon dioxide, aluminum nitride, boron nitride, zirconium oxide, aluminum oxide, etc. having a particle size of 1 nm to 700 nm. The particles contained in the inorganic filler may be surface treated with a silane coupling agent or the like.

[0109] When an inorganic filler is used, the content thereof is usually 10 to 90 parts by mass, preferably 20 to 80 parts by mass, based on 100 parts by mass of the entire solid content.

[0110] <Adhesive sheet>

[0111] The adhesive composition of the present invention is applied onto a release substrate (eg, a PET film coated with a silicone release layer) serving as a base film by bar coating, slit coating, inkjet coating, etc., and then pre-dried in an oven or the like to form a coating film.

[0112] As the conditions for the heat treatment, for example, a heating temperature and a heating time appropriately selected from the range of 70 to 160° C. and 0.3 to 60 minutes are adopted. The heating temperature and the heating time are preferably 80 to 140° C. and 0.5 to 10 minutes.

[0113] Then, a release substrate for a protective film is attached to the coating film of the composition to obtain an adhesive sheet. The coating film and the protective film are pressed together in a certain direction using a manual or automatic laminating roller so that air bubbles do not enter between them to obtain an adhesive sheet.

[0114] By processing the adhesive sheet into any size, the adhesive composition can be formed into a film only at the desired location on the array substrate. After processing into any size, the protective film is peeled off, and its peeled surface is attached to a specified location, and the base film is peeled off, thereby transferring the adhesive composite film to the substrate. In order to improve the adhesion between the composite film and the substrate, transfer under pressure is also effective.

[0115] In order to peel the protective film well from the coating surface, it is necessary to reduce the peel strength of the protective film and increase the peel strength of the base film. The peel strength of the protective film is preferably 80N / 25mm or less, and the peel strength of the base film is preferably 160N / 25mm or more.

[0116] <Cured film>

[0117] Next, such a pattern-formed film is post-baked for thermal curing, specifically, heated using a hot plate, an oven, etc., thereby obtaining a film having excellent heat resistance, transparency, planarization properties, low water absorption, chemical resistance, etc. and having a good pattern.

[0118] The post-baking is generally carried out at a heating temperature selected from the range of 140 to 270° C. for 5 to 30 minutes on a hot plate or for 30 to 90 minutes in an oven.

[0119] Then, by such post-baking, a cured film having a desired good pattern shape can be obtained.

[0120] The film obtained from the adhesive composition of the present invention has fluxing properties and adhesive properties, and the film can be processed arbitrarily to form the film only at a desired location on the array substrate.

[0121] After transferring a large number of LED elements to an array substrate with an adhesive composite film, a flip chip bonding machine is used to heat and press (in order to melt the solder electrode, the heating temperature is usually in the range of 250 to 350°C), thereby bonding the array electrode to the LED element electrode. During the heating and pressing, the composite film is in an uncured state, so it becomes molten by heating, and by applying pressure, the composite film is repelled from the array electrode and the LED element electrode, and does not hinder the bonding between the electrodes. Then, by thermally curing the composite film repelled to the periphery of the electrode, it functions as a bottom filling material that protects the periphery of the electrode from air and moisture.

[0122] It should be noted that the adhesive composition of the present invention is unlikely to turn yellow even when subjected to a high-temperature process during flip-chip bonding and has high transparency, and therefore is unlikely to impair the color purity of an LED element.

[0123] Example

[0124] Hereinafter, the present invention will be described in further detail with reference to Examples, but the present invention is not limited to these Examples. The abbreviations of the compounds used, the release substrates, and the methods for measuring the properties are as follows.

[0125] (monomer)

[0126] HQMA: p-Hydroxyphenyl methacrylate.

[0127] HEMA: 2-hydroxyethyl methacrylate.

[0128] BA: n-butyl acrylate.

[0129] (Free Radical Polymerization Initiator)

[0130] AIBN: α, α'-azobisisobutyronitrile.

[0131] (Isocyanurate compound)

[0132] I1: NK Ester A-9300 (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.).

[0133] I2: TEPIC-VL (manufactured by Nissan Chemical Co., Ltd.).

[0134] (Epoxides)

[0135] E1: EPOCHALIC DE-102 (manufactured by ENEOS Corporation).

[0136] E2: EHPE 3150 (manufactured by Daicel Corporation).

[0137] E3: jER152 (manufactured by MITSUBISHI CHEMICAL Co., Ltd.).

[0138] E4: EPOLEAD GT-401 (tetrakis(3,4-epoxycyclohexylmethyl)butanetetracarboxylic acid ester-modified ε-caprolactone, manufactured by Daicel Corporation).

[0139] E5: CELLOXIDE 2021P (manufactured by Daicel Co., Ltd.).

[0140] E6: DENACOL EX-851 (manufactured by Nagase ChemteX Corporation).

[0141] E7: Shofree BATG (manufactured by RESONAC Co., Ltd.).

[0142] (Inorganic filler)

[0143] F1: Organic silica sol MEK-AC-5140Z (manufactured by Nissan Chemical Co., Ltd.).

[0144] (Solvent)

[0145] PGME: Propylene glycol monomethyl ether.

[0146] IPA: Isopropyl alcohol.

[0147] (Peeling substrate)

[0148] Base film: PET film (manufactured by NIPPA Corporation) coated with a silicone release layer and having a peel strength of 380 N / 25 mm.

[0149] Protective film: PET film (manufactured by NIPPA Corporation) coated with a silicone release layer having a peel strength of 40 N / 25 mm.

[0150] <Determination of molecular weight>

[0151] The molecular weight of the polymer was measured as follows using a room temperature gel permeation chromatography (GPC) apparatus (GPC-101) (manufactured by Showa Denko K.K.) and columns (KD-803 and KD-805 connected in series) (manufactured by Showa Denko K.K.).

[0152] Column temperature: 50°C.

[0153] Eluent: N,N-dimethylformamide (as additives, lithium bromide monohydrate (LiBr·H2O) at 30 mmol / L (liter), phosphoric acid·anhydrous crystals (o-phosphoric acid) at 30 mmol / L, tetrahydrofuran (THF) at 10 mL / L).

[0154] Flow rate: 1.0 ml / min.

[0155] Standard samples for preparing the calibration curve: TSK standard polyethylene oxide (molecular weight: about 900,000, 150,000, 100,000 and 30,000) (manufactured by TOSOH) and polyethylene glycol (molecular weight: about 12,000, 4,000 and 1,000) (manufactured by Polymer Laboratories).

[0156] <Measurement of glass transition temperature (Tg)>

[0157] The Tg of the polymer obtained in the Synthesis Example was measured under the following conditions using differential scanning calorimetry (DSC) DSC1 (manufactured by METTLER TOREDO).

[0158] Heating rate: 10℃ / min.

[0159] Measuring temperature: -20℃~200℃.

[0160] Number of measurements: Twice. Tg is calculated based on the second temperature rise result.

[0161] <Synthesis of acrylic polymer>

[0162] (Synthesis example 1)

[0163] HQMA (6.0 g), HEMA (4.0 g) and BA (10.0 g) were used as monomer components constituting an acrylic polymer, and AIBN (0.2 g) was used as a free radical polymerization initiator. They were subjected to polymerization reaction in a solvent PGME (47.1 g) at a temperature of 60° C., thereby obtaining a solution P1 of an acrylic polymer component having a Mn (number average molecular weight): 24700 and a Mw (weight average molecular weight): 111900 (acrylic polymer concentration: 30.0% by mass). The solution P1 was applied on a 5 cm×5 cm glass substrate using a spin coater, and then pre-baked on a hot plate at a temperature of 100° C. for 120 seconds to obtain a dried film of the acrylic polymer. The Tg of the obtained acrylic polymer was 31° C.

[0164] (Synthesis example 2)

[0165] HQMA (10.0 g) and BA (10.0 g) were used as monomer components constituting an acrylic polymer, and AIBN (0.06 g) was used as a free radical polymerization initiator. They were subjected to a polymerization reaction in a solvent PGME (46.8 g) at a temperature of 60° C., thereby obtaining an acrylic polymer P2 (acrylic polymer concentration: 30.0 mass %) having a molecular weight and Tg as shown in Table 1.

[0166] (Synthesis example 3)

[0167] HQMA (14.0 g) and BA (6.0 g) were used as monomer components constituting an acrylic polymer, and AIBN (0.2 g) was used as a free radical polymerization initiator. They were subjected to a polymerization reaction in a solvent PGME (37.5 g) at a temperature of 60° C., thereby obtaining an acrylic polymer P3 (acrylic polymer concentration: 35.0 mass %) having a molecular weight and Tg as shown in Table 1.

[0168] [Table 1]

[0169]

[0170] <Preparation of Adhesive Composition>

[0171] (Example 1-1)

[0172] To the acrylic polymer solution (P1) (4.167 g) obtained in the above-mentioned synthesis example 1 as a resin solution, an isocyanurate compound I1 (0.375 g), an epoxy compound E1 (0.375 g) and a solvent PGME (2.683 g) and IPA (2.400 g) were added, and the mixture was stirred at room temperature for 2 hours to prepare an adhesive composition V1 having the composition shown in Table 2.

[0173] (Examples 1-2 to 1-5) and (Comparative Examples 1-1 to 1-4)

[0174] The types and amounts of the resin solution, isocyanurate compound, epoxy compound and solvent were changed as shown in Table 2 and added, followed by stirring at room temperature for 2 hours to prepare positive photosensitive adhesive compositions V2 to V5 and RV1 to RV4 having the compositions shown in Table 2.

[0175] (Examples 1-6)

[0176] After adding isocyanurate compound I2 (0.623 g), epoxy compound E2 (0.623 g), inorganic filler F1 (2.144 g) and solvent PGME (3.752 g) to acrylic polymer resin solution (P2) (2.857 g), stirring was carried out at room temperature for 2 hours to prepare adhesive composition V6 with the composition shown in Table 2.

[0177] [Table 2]

[0178]

[0179] (Example 2-1)

[0180] <Adhesion evaluation>

[0181] After applying the adhesive composition V1 prepared in Example 1-1 on a 5 cm × 5 cm glass substrate using a spin coater, it was pre-baked on a hot plate at a temperature of 100°C for 120 seconds to form a pre-baked film with a thickness of 3 μm. Then, using a texture analyzer manufactured by Stable Micro Systems, the peel strength of the coating surface at room temperature (23°C) was measured using a probe ball (diameter: 25 mm, material: SUS), compression speed: 1 mm / sec, tensile speed: 1 mm / sec, compression load: 200 g, and compression holding time: 2 sec. If the peel strength is 1.0 g or more, it is judged that the adhesion is good, and if the peel strength is less than 1.0 g, it is judged that the adhesion is poor. The results are recorded in Table 3.

[0182] <Transmittance evaluation>

[0183] After applying the adhesive composition V1 prepared in Example 1-1 on a quartz substrate of 4 cm×4 cm using a spin coater, it was pre-baked on a hot plate at a temperature of 100°C for 120 seconds to form a pre-baked film with a film thickness of 3 μm. Assuming that the heat provided to the organic film during flip-chip bonding is applied to the pre-baked film, it was heated on a hot plate at a temperature of 300°C for 60 seconds. Then, it was post-baked on a hot plate at a temperature of 230°C for 30 minutes to form a cured film. The transmittance of the obtained cured film was measured, and the case where the average value in the visible region (wavelength 400nm~800nm) was 95% or more was evaluated as good transparency, and the case where the average value in the visible region (wavelength 400nm~800nm) was less than 95% was evaluated as poor transparency. The results are recorded in Table 3.

[0184] (Examples 2-2 to 2-6 and Comparative Examples 2-1 to 2-4)

[0185] Adhesion and transparency were evaluated by the same method as in Example 2-1 using adhesive compositions V2 to V6 and RV1 to RV4 prepared in Examples 1-2 to 1-6 and Comparative Examples 1-1 to 1-4. The prebaking conditions were appropriately changed to a temperature of 100 to 140° C. and a time of 2 to 10 minutes.

[0186] The results are recorded in Table 3.

[0187] [Table 3]

[0188]

[0189] As shown in Table 3, the adhesive compositions of the examples all showed good adhesiveness and transparency. In contrast, when an adhesive composition using an acrylic polymer having a glass transition temperature (Tg) of 100°C or higher was used (Comparative Example 2-3) or when no isocyanurate compound was used (Comparative Example 2-2), the adhesiveness was insufficient. In addition, when the epoxy compound used had an aromatic ring (Comparative Examples 2-1 and 2-4), the transparency was insufficient.

[0190] (Example 3-1)

[0191] <Diaphragm production and evaluation>

[0192] After applying the adhesive composition V1 prepared in Example 1-1 on an A4-sized base film using a rod coater, it was pre-baked in an oven at a temperature of 100°C for 120 seconds to form a pre-baked film with a film thickness of 3 μm, and then the protective film was laminated to the pre-baked film using a roller to produce an adhesive sheet S1. Then, the peelability of the protective film was evaluated. After peeling off the protective film, if there is no film residue on the protective film side, it is judged to be good, and if a part of the adhesive composition remains on the protective film side, it is judged to be poor. Next, the transferability from the base film to the substrate is evaluated. A glass substrate of 5 cm × 5 cm and 1 mm in thickness is used as the substrate. After peeling off the base film, if there is no film residue on the base film side and the adhesive sheet is transferred to the substrate without wrinkles, it is judged to be good, and if a part of the adhesive composition remains on the base film side or wrinkles are generated on the adhesive sheet after transfer, it is judged to be poor. Finally, a texture analyzer manufactured by Stable Micro Systems was used with a probe ball (diameter: 25 mm, material: SUS), compression speed: 1 mm / sec, tension speed: 1 mm / sec, compression load: 200 g, compression holding time: 2 sec The peel strength of the coating film surface at room temperature (23° C.) was measured. If the peel strength was 1.0 g or more, the adhesion was judged to be good, and if the peel strength was less than 1.0 g, the adhesion was judged to be poor. The results are recorded in Table 4.

[0193] (Example 3-2)

[0194] Using the adhesive composition V2 prepared in Example 1-2, an adhesive sheet S2 was prepared in the same manner as in Example 3-1, and the peelability of the protective film, the transferability to the substrate, and the adhesiveness of the sheet were evaluated.

[0195] [Table 4]

[0196] Adhesive sheet Peelability evaluation Transferability evaluation Adhesion evaluation Example 3-1 S1 good good good Example 3-2 S2 good good good

[0197] (Examples 4-1, 4-2)

[0198] <Flip chip bonding test>

[0199] As a mounting sample, a TEG (Test Element Group) chip (5.1 mm × 5.1 mm × 700 μm thick) having 1700 electrodes with an electrode area of ​​20 μm × 20 μm and an electrode height of 5.5 μm (the height of the SnAg solder is 2.3 μm, and the height of the copper pillar electrode is 3.2 μm) and a TEG substrate (15 mm × 15 mm × 700 μm thick) with copper electrodes wired in a daisy chain with the electrodes of the TEG chip were prepared. The adhesive sheets prepared in Examples 3-1 and 3-2 were transferred to the TEG substrate to form an underfill film. Next, a flip chip bonder manufactured by Panasonic was used to perform flip chip bonding on the TEG substrate having the underfill film at a table temperature of 60°C, a head temperature of 370°C, for 60 seconds, and a head pressure of 150N. Then, post-baking (post-curing) was performed at 230°C for 30 minutes to obtain a bonded body. The obtained bonded body was evaluated for the presence or absence of TEG chip peeling (no peeling: ○, peeling: ×) and the on-resistance value (less than 100Ω: ○, 100Ω or more: ×). The results are recorded in Table 5.

[0200] (Comparative Example 4-1)

[0201] Before flip chip bonding, the TEG chip and TEG substrate were cleaned with a 5 mass % sulfuric acid aqueous solution to remove the surface oxide film instead of using the adhesive sheet as the bottom filling film. The joint body was formed in the same manner as in Example 4-1, and the presence or absence of TEG chip peeling was confirmed and the on-resistance value was measured. The results are recorded in Table 5.

[0202] [Table 5]

[0203]

[0204] As shown in Table 5, the TEG chip of the TEG junction body using the adhesive sheet of the example as the underfill film did not peel off and had a good on-resistance value. In contrast, when no underfill film was used, the peeling of the TEG chip increased significantly and the resistance value could not be measured reproducibly and well (Comparative Example 4-1).

Claims

1. An adhesive composition comprising the following components A, B, C and D, Component A: an alkali-soluble resin having a phenolic hydroxyl group and a polymer having a glass transition temperature Tg of 60°C or less; Component B: a compound having an isocyanurate skeleton; Component C: aliphatic or alicyclic epoxy compound; Component D: solvent.

2. The adhesive composition according to claim 1, wherein The component A is a polymer including a structural unit derived from a monomer A2 having a homopolymer Tg of 0° C. or less.

3. The adhesive composition according to claim 2, wherein The component A is an acrylic polymer containing structural units derived from a monomer A1 having a phenolic hydroxyl group and a polymerizable unsaturated group and a monomer A2 having a homopolymer Tg of 0° C. or less as constituent components.

4. The adhesive composition according to claim 3, wherein The monomer A1 having a phenolic hydroxyl group and a polymerizable unsaturated group is selected from the group consisting of p-hydroxystyrene, m-hydroxystyrene, α-methyl-p-hydroxystyrene and a compound represented by the following formula (1). P—b1-c1-d1 (1) In formula (1), P represents a (meth)acryloyl group, a (meth)acrylamide group, an N-methyl(meth)acrylamide group or a maleimide group, b1 represents a single bond, or an alkylene group consisting of a linear, branched or cyclic group having 1 to 12 carbon atoms or a combination thereof, c1 represents a single bond, -O-, -COO- or -OCO-, and d1 represents a substituted or unsubstituted hydroxyphenyl group.

5. The adhesive composition according to claim 3 or 4, wherein The monomer A2 whose homopolymer Tg is below 0°C is a compound represented by the following formula (2): In formula (2), R2 represents a hydrogen atom or a methyl group, a2 represents an oxygen atom or a sulfur atom, b2 represents an alkylene group consisting of a straight chain, branched chain or cyclic group or a combination thereof having 2 to 20 carbon atoms, and the -CH2- in the alkylene group is optionally substituted by an oxygen atom on the premise that they are not adjacent to each other; c2 represents a single bond, -O-, -COO- or -OCO-, and d2 represents a hydrogen atom or a hydroxyl group.

6. The adhesive composition according to any one of claims 1 to 5, wherein The amount of component B is 20 to 100 parts by mass based on 100 parts by mass of component A.

7. The adhesive composition according to any one of claims 1 to 6, wherein The amount of the component C is 10 to 100 parts by mass based on 100 parts by mass of the component A.

8. The adhesive composition according to any one of claims 1 to 7, wherein The surfactant is further contained as the E component in an amount of 0.01 to 1.0 parts by mass based on 100 parts by mass of the A component.

9. The adhesive composition according to any one of claims 1 to 8, wherein An inorganic filler is further contained as the F component.

10. An adhesive sheet comprising the adhesive composition according to any one of claims 1 to 9 laminated on both sides with a release substrate. 11 . A cured film obtained by curing the adhesive composition according to claim 1 . 12 . An LED display element having the cured film according to claim 11 as an underfill material.